DETERMINAN INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Erlynda Diah Hidayati, 14.05.52.0197; Badjuri, Achmad (Students Journal of Accounting and Banking, 2018)
The purpose of this study examines the effect of institutional ownership, managerial ownership, independent commissioner, audit committee, audit quality, audit tenure and firm size on the integrity of financial statements. This research was conducted at manufacturing company listed on Indonesia Stock Exchange (BEI). The sampling method used in this study is purposive sampling with observation period 2014 to 2016 the number of samples obtained as much as 84. Relationship and (or) influence between variable is discribed by using multiple regression analysis with SPSS 21 program. The type of data used is secondary data. The results showed that audit committee, audit quality, and firm size influences significantly positive on the integrity of financial statements. While institutional ownership, managerial ownership, independent commissioners and audit tenure do not significantly affect the integrity of financial statements.Keywords: The Integrity of Financial Statement, Institutional Ownership, Managerial Ownership, Independent Commissioner, Audit Committee, Audit Quality, Audit Tenure and Firm Size